Późnoantyczna Tarraco. Kontynuacja i zmiana w przestrzeni miejskiej (III–V wiek) - Zimnowodzka, Anna (Collectanea Philologica, 2022)
Established in the 3rd century BCE, Tarraco reached its heyday in the 2nd century (AD). In the second half of the 2nd and at the beginning of the following century, despite the noticeable progressive recession of the city (abandonment of the theater and the nymphaeum, decrease of artistic activities), selected buildings and districts in the city were still flourishing (including the port area, the temple of Augustus and the amphitheater). The process of transformation of the city proceeded slowly, even in the 4th century, when the forum of the colonies was abandoned, some buildings, including the Concilium Provinciae Hispaniae Citerioris, continued to perform their functions. In the 5th century, as evidenced by epigraphy, a part of the square was still used for representative purposes, with the rest of it being replaced by residential buildings. The circus was still in use until the middle of the 5th century. The demolition, in the second half of the 5th century, of the temple of Augustus, which dominated the city, and the gradual erection of Christian basilicas, first outside the city and from the 6th century onwards, also within it, marked the end of an era in the history of the city.